Analisis Hukum Terhadap Prinsip Kehati-Hatian dan Penilaian Tingkat Kesehatan Bank pada Perbankan Syariah - Afif Khalid; Dadin Eka Saputra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research discusses the principle of prudence in Islamic banking and the level of health implemented. This research uses normative legal research by examining the research approach used is conceptual approach. This prudential principle must be carried out by banks, not only because it is associated with obligations so that banks do not harm the interests of customers This evaluation aims to enable the public to assess the performance of an Islamic bank. A bank that is considered healthy is a bank that can run its operations smoothly, fulfill its financial obligations, ensure the security of funds placed by the public, and has the ability to develop the resources that have been entrusted by the owner to its management.